Growth characteristics and saponin content of mountain-cultivated ginseng (Panax ginseng C. A. Meyer) according to seed-sowing method suitable for cultivation under forest - Seong Hyeon Yong (Forest Science and Technology, 2020)
Mountain-cultivated ginseng (MCG) is a very important health functional material in Korea and the USA. In this study, the growth and saponin of MCG change according to the sowing method were investigated. Six methods of sowing according to the natural cultivation method that grows in the Sancheong mountain ginseng farm were investigated. Germination rate and budding rate were different according to the sowing method. The growth characteristics of the MCG were also different in the sowing method. Among the six sowing methods, the length of leaves was the widest in BFS. The width of the leaves was wide in DFS and DS. The weight of the shoot was the heaviest in BFS, and the DF was the lightest. Root diameter was highest in BFS and DFS covering both fallen leaves and soil. Total fresh weight was the highest at 4.03 g in BFS, followed by DFS. The S/R ratio of DF was lower than that of the other methods. This suggests that the S/R ratio is lowered because the growth of the ground part is worse. The treatment group with the highest crude saponin content was BF and the lowest treatment group was BS. Shoot and root growth tended to increase with growing period, saponin content increased slightly within 1–3 years, but decreased slightly after that. In particular, the ratio of PD/PT, which has a great influence on the efficacy of ginseng, was also different according to the sowing method. The seed sowing method identified in this study will greatly contribute to the improvement of the survival rate decrease over the cultivation period, and it will also contribute to the production of high-quality MCG.